Potensi Enzim Superoksida Dismutase dari Biji Jagung (Zea Mays L.) untuk Perbaikan Sel Fibroblas 3t3 Yang Dipaparkan Sinar Ultraviolet A - Mustika Endah Pratiwi; Jason Merari Peranginangin; Isna Jati Asiya; Ana Indrayati (Universitas Islam Indonesia, 2022)
Background: UV-A radiation induct disorder to the skin called photoaging. It requires treatment with antioxidant agent. Superoxide dismutase (SOD) is the first line antioxidant in the treatment of free radicals. Objective: This study aimed to find out anti-photoaging activities of SOD extract of corn (Zea mays L.) kernels on radiated UV-A rays 3T3 fibroblast cells. Method: SOD extraction of corn kernels was done by centrifugation, precipitation and dialysis method. The activity of SOD extract in corn kernels was measured by WST-1 method. Anti-photoaging activity test of SOD extract in corn kernels was done on radiated UV-A rays 3T3 fibroblast cells with parameters of cell viability. Anti-photoaging activity test using cell control, negative, sample and positive control. Results: SOD activity showed that the highest percent inhibition value was SOD extract of corn kernels in precipitation of ammonium sulphate concentration was 60-90% with inhibition percentage was 65.50%. The result of anti-photoaging activity SOD extract of corn kernels showed significant difference in the value of percent cell viability in fibroblast cells between the extract group and the negative control group with the highest percent cell viability in SOD extract corn kernels with the concentration was 100 mg/mL, namely 142.31%. Conclusion: SOD extract from corn kernels has proven had antioxidant activity that could be used as anti-photoaging through fibroblast cell reparation mechanism.